Evaluación técnico-financiera mediante pruebas de laboratorio del uso de microesferas huecas de vidrio en fluido de perforación base agua para Campo Castilla (2017)
The Castila Field, located in the Eastern Plains Basin and located in the department of Meta, currently has high losses of circulation of drilling fluid due to the fractures that present their formations and to the overbalance drilling that is performed. To continue drilling projects, Halliburton Latin America saw the need to evaluate an additive that reduces the density of drilling fluid currently used to mitigate circulation losses in the Castilla Field. The project arose from this initiative for the evaluation of the additive Glass Hollow Microspheres as a density reducer.